Analysis of micropolar elastic multi-laminated composite and its application to bioceramic materials for bone reconstruction - Rodríguez Ramos, Reinaldo; Espinosa-Almeyda, Yoanh; Camacho Montes, Hector; Guinovart Sanjuán, David; Rodríguez Bermúdez, Panters; Brito Santana, Humberto; Otero Hernández, Jose Antonio; Sabina Ciscar, Federico Juan (2024)
The asymptotic homogenization method is applied to characterize the effective behaviour of periodic multi-laminated micropolar elastic heterogeneous composites under perfect contact conditions. The local problem formulations and the analytical expressions for the effective stiffness and torque coefficients are derived for the centrosymmetric case.